2022
DOI: 10.4236/pp.2022.1310029
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing Patterns in Adult Patients According to the WHO AWaRe Classification: A Multi-Facility Cross-Sectional Study in Primary Healthcare Hospitals in Lusaka, Zambia

Abstract: Introduction: Indiscriminate prescribing and using of antibiotics have led to the development of antimicrobial resistance (AMR). To reduce this problem, the World Health Organization (WHO) developed the "Access", "Watch", and "Reserve" (AWaRe) classification of antibiotics that promotes antimicrobial stewardship (AMS). In Zambia, there are gaps in practice regarding prescribing of antibiotics based on the AWaRe protocol. This study assessed antibiotic prescribing patterns in adult in-patients in selected prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 66 publications
1
17
1
Order By: Relevance
“…Notable is that despite the high prevalence of 3GC resistance in our setting, as was also noted in previous studies [17,18,21], there has limited guidance based on institutional surveillance and formulation of institution/unit-specific antibiogram guidelines until recently in 2022 [21]. A recent multi-facility cross-sectional study that reviewed and analysed the antibiotic prescribing patterns in adult patients at primary healthcare hospitals in Zambia found ceftriaxone (20.3%) to be the most prescribed antibiotic [35]. Although lower than what was previously recorded at the UTH, most primary healthcare hospitals in Zambia lack fully functional diagnostic laboratories that perform culture and antimicrobial…”
Section: Plos Global Public Healthmentioning
confidence: 68%
See 1 more Smart Citation
“…Notable is that despite the high prevalence of 3GC resistance in our setting, as was also noted in previous studies [17,18,21], there has limited guidance based on institutional surveillance and formulation of institution/unit-specific antibiogram guidelines until recently in 2022 [21]. A recent multi-facility cross-sectional study that reviewed and analysed the antibiotic prescribing patterns in adult patients at primary healthcare hospitals in Zambia found ceftriaxone (20.3%) to be the most prescribed antibiotic [35]. Although lower than what was previously recorded at the UTH, most primary healthcare hospitals in Zambia lack fully functional diagnostic laboratories that perform culture and antimicrobial…”
Section: Plos Global Public Healthmentioning
confidence: 68%
“…This use of 3GCs in primary care facilities promotes the emergence of 3GC-resistant pathogens thereby further limiting treatment options for patients being referred to tertiary hospital where 3GCs are widely used as empiric treatment [36]. Similar to the findings at the UTH and the primary care facilities in Lusaka [35,36], another study in Zambia that reviewed antibiotic use and stewardship indicators in the first-and second-level hospitals in ten provinces at ten different hospitals found the prevalence of antibiotic use among the in-patients to be at 59% with a high rate of empiric prescribing (97%), of which ceftriaxone was 36% of all antibiotics prescribed [37]. Low compliance to the national standard treatment guidelines (STGs), low justified antibiotic use at 16% and only 3% of the treatment having been guided by microscopy, culture and sensitivity (MCS).…”
Section: Plos Global Public Healthmentioning
confidence: 72%
“…In Zambia, there are gaps and lack of knowledge among healthcare workers on the use the AWaRe tool because studies have reported high prescribing of Watch antibiotics. 7 , 8 , 10 In all studies, ceftriaxone, a Watch antibiotic, was being overused (Table 1 ). This contrasts with the WHO recommendations.…”
Section: Experiences In Zambia On the Use Of The Aware Classification...mentioning
confidence: 99%
“…The inappropriate use of antibiotics in humans and animals has contributed to the development and worsening of AMR . One of the major factors contributing to AMR in humans has been reported to be the ease with which antimicrobials can be obtained without a prescription. Additionally, irrational prescribing of antibiotics has made this phenomenon worse. , AMR has also been linked to irrational dispensing practices and easy access to antibiotics for use in animals without a prescription. Evidence has also shown that healthcare professionals with this responsibility have missed doses when administering antibiotics, which has been linked to the development of AMR. , As a result, patient noncompliance with antimicrobial therapy has also contributed to the development of AMR. Furthermore, a lack of patient education on antimicrobial use (AMU) and AMR is another factor that contributes to inappropriate AMU and, eventually, may lead to the development of AMR. ,, …”
Section: Introductionmentioning
confidence: 99%
“… 29 31 Additionally, irrational prescribing of antibiotics has made this phenomenon worse. 25 , 32 38 AMR has also been linked to irrational dispensing practices and easy access to antibiotics for use in animals without a prescription. 39 42 Evidence has also shown that healthcare professionals with this responsibility have missed doses when administering antibiotics, which has been linked to the development of AMR.…”
Section: Introductionmentioning
confidence: 99%